Comparison of an Italian Chart with an Iranian Chart in Visual Acuity Measurement - Haleh Kangari; Alireza Akbarzadeh Bagheban; Atiyeh Khomamizadeh; Saeed Rahmani (Novelty in Biomedicine, 2015)
Background: Taking visual acuity is an important part of an eye routine examination. This study was conducted to compare visual acuity measured using an Iranian digital tumbling E chart with visual acuity measured using an Italian digital tumbling E chart as a familiar foreign chart. Materials and Methods: This study was carried out on 200 participants (400 eyes; healthy n=40, glaucoma n=40, retinal disorders n=40, post lasik n=40, corneal n=40) with mean age 44.28 years. Visual acuity of both eyes of half of the subjects (n=100, n=20 from each group), was first measured using the Italian digital chart and then measured using Iranian digital chart. Visual acuity of the rest of subjects (n=100, n=200 from each group) was first measured using the Iranian digital chart and then measured using the Italian digital chart. Measured visual acuities were recorded in logMAR notation. Results: The mean of the Iranian and Italian Tumbling E chart is 0.280±0.012 and 0.277±0.012, respectively. Paired t-test used to evaluate the mean difference between two groups (p=0.721) indicated that there was no statistically significant difference between means of the two tests. Spearman correlation coefficient for the results of both tests was 0.942 (p<0.001), which was statistically significant and could be categorized as a strong positive correlation. Conclusion: The two digital Tumbling E charts acted similarly at different levels of acuity in different disorders. However, the Iranian chart requires a more accurate design for optotypes of the lower acuity lines in order to obtain more accurate measurement of visual acuities in healthy subjects.